Youth Representative of Verbal and Visual Signs on Music Concert Posters: A Semiotic Analysis - Manu, Bagus Rama Dharma; Hikmaharyanti, Putu Desi Anggerina (Humanis; Vol 28 No 2 (2024), 2024)
Music concert posters serve as vital visual representations of youth culture, capturing their creative essence. This study examines three 2023 Bali concert posters, analysing verbal and visual signs. Using Saussure's framework from Chandler (2007), verbal and nonverbal signs are explored, while Barthes (1977) was used to delve into denotative and connotative meanings. Cerrato's (2012) color theory adds depth through color analysis. The analysis reveals prevalent verbal signs, but profound meanings lie in visual cues, suggesting modern youth's preference for visually engaging content. Interestingly, these posters also integrate indigenous elements and local characteristics, melding youthful expression with cultural context by adding cultural figures and authentic colours reflected the message conveyed on the posters.